2018
DOI: 10.1515/ling-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries of null subjects and null objects in L1-English and L1-Japanese learners’ Chinese

Abstract: Based on the HSK Dynamic Composition Corpus, this study investigated the use of Chinese null arguments by advanced adult L1-English and L1-Japanese learners with Chinese native speakers as a baseline. Several asymmetries were found. First, the learners produced many more null subjects than null objects. Second, null subjects were mainly animate, while null objects were mainly inanimate. Third, more null subjects were used in non-matrix clauses than in matrix clauses. In addition, L1 did not seem to play a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…There have been a few studies focused on Kurdish EFL learners' writing errors in the Iraqi Kurdistan Region, but none have been able to show the precise kinds of errors the learners make when writing English. For instance, Chen (2004) looked at the English writing mistakes made by Chinese ESL students. His study found that students brought grammatical elements from the Chinese language to the English language.…”
Section: Previous Studiesmentioning
confidence: 99%
“…There have been a few studies focused on Kurdish EFL learners' writing errors in the Iraqi Kurdistan Region, but none have been able to show the precise kinds of errors the learners make when writing English. For instance, Chen (2004) looked at the English writing mistakes made by Chinese ESL students. His study found that students brought grammatical elements from the Chinese language to the English language.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In short, Brown (2000) concluded that overgeneralizing the target language might lead to errors in learning English. Chen (2004) published a report on 710 Hong Kong Chinese ESL learners in Hong Kong. Of the five common types of errors found, there are five.…”
Section: Types Of Errors In Writingmentioning
confidence: 99%